Impact of co-epidemic tuberculosis and diabetes mellitus on health-related quality of life: A review - Machrumnizar, Machrumnizar; Muyana, Nana; Bachtiar, Adang; Kusumaratna, Rina Kurniasri; Suyanto, Jipri (Universitas Aisyah Pringsewu, 2023)
The high comorbidity rate between diabetes mellitus and tuberculosis has a significant impact on the patient's health-related quality of life and eradication of tuberculosis program outcomes, especially in lower-middle-income countries that bear a